Librarians Are Interested in Finding Research Collaborators - Kaari, Jennifer (Evidence Based Library and Information Practice, 2021)
A Review of: Tran, N. Y., & Chan, E. K. (2020). Seeking and finding research collaborators: An exploratory study of librarian motivations, strategies, and success rates. College & Research Libraries, 81(7), 1095. https://doi.org/10.5860/crl.81.7.1095 Abstract Objective – To explore research collaboration among librarians, including librarians’ motivations for collaboration, methods for finding collaborators, and how they perceive the success of these methods. Design – Online survey questionnaire. Setting – N/A Subjects – A total of 412 librarians took the survey, and 277 respondents completed the entire survey. Methods – The researchers developed a survey using Qualtrics, including questions focused on whether respondents had sought research collaboration, factors that motivated them to collaborate, methods they used for finding collaborators, and success rates of these methods. Demographic questions were also included. Main Results – The survey results indicated that librarians are very interested in research collaboration, with 91.8% of respondents answering that they had sought collaborators, were currently collaborating, or were interested in seeking collaborators in the future. The top motivating factor for seeking collaboration was to gain expertise that the respondent lacked. The most common strategy for finding collaborators was through a respondent’s current or past place of employment, and this method was rated as extremely successful by more than 50% of respondents. Demographically, 70.1% of respondents worked in academic libraries. Conclusion – The results of this study indicate that research collaboration is of interest to librarians at a higher rate than previously observed. These results can help inform initiatives to support and promote collaboration in library and information science research, as well as provide a groundwork for further research in this area.